Cost Accounting : an essential guide - Russell, David, 1963-; Patel, Ashok, ....-; Wilkinson-Riddle, Gregory, ....- (Harlow, England : Prentice Hall, 2002)
This new text provides a concise and clear introduction to the core principles of cost accounting. It sets out to make the key principles of the subject accessible to those with no prior knowledge and avoids detailed coverage of specific costing methods, making it the ideal first text for students wishing to grasp the basics of what can be a complex and diverse subject.
Keywords: Kostencalculatie